KEMAMPUAN MEMBUAT MOOD BOARD TERHADAP PRESTASI MENGGAMBAR DESAIN BUSANA MAHASISWA DI AKS AKK YOGYAKARTA - Purwani, Sri (Jurnal Socia Akademika, 2024)
In Indonesia, student education is increasingly advancing as part of the effort to produce competent and creative professionals. One institution focusing on vocational education in this field is AKS AKK Yogyakarta. As a vocational higher education institution, AKS AKK plays a significant role in providing relevant and applicable skills to its students. In this context, students' ability to create mood boards is considered essential, as it serves as a foundation for broader academic and creative processes. This study adopts a quantitative approach with a true experimental design. The chosen design is the Pretest-Posttest Group Design. The population of this study consists of all students in the Fashion Design program at the Social Welfare Academy (AKK) Yogyakarta during the relevant academic year. The sample was selected using a simple random sampling technique, taking into account the homogeneity of students’ initial abilities, with a total of 40 students participating in a Drawing Achievement Test. Data analysis was conducted using a t-test. The results indicate a significant influence of the ability to create mood boards on the academic performance of students in the Fashion Design program at AKS AKK Yogyakarta. Thus, it can be concluded that the ability to create mood boards has a positive contribution to enhancing students’ academic performance.